Woman, I go on writing your name... On the feminization of names of professions, titles, degrees and functions - Janoušková, Jitka (Romanica Olomucensia, 2015)
This article deals with the controversial topic of the linguistic feminization of French. First, it concentrates on the relationship between a language and a society and subsequently it recapitulates the approaches and political steps taken in France and the Francophone regions of Belgium, Switzerland and Canada. Second, it summarizes the results of diverse studies on the effects of this feminization so that progress in this matter can be evaluated. Part of the article is devoted to a lexical analysis carried out in a French web corpus.
Keywords: linguistic feminization; professions; language; society; discrimination.